Acetylation-dependent regulation of TPD52 isoform 1 modulates chaperone-mediated autophagy in prostate cancer. Issue 12 (2nd December 2021) - Fan, Yizeng; Hou, Tao; Gao, Yang; Dan, Weichao; Liu, Tianjie; Liu, Bo; Chen, Yule; Xie, Hongjun; Yang, Zhao; Chen, Jiaqi; Zeng, Jin; Li, Lei
ABSTRACT: Aberrant chaperone-mediated autophagy (CMA) activation has been suggested as a tumorigenesis-promoting event in various cancers, although its roles in prostate cancer (PCa) remain elusive. Emerging evidence indicates that TPD52 isoform 1, a prostate-specific and androgen-responsive gene, contributes to the malignant progression of PCa. Here, we demonstrate that TPD52 enhances CMA activation by interacting with HSPA8/HSC70 and enhancing substrate degradation in PCa. Elevation of TPD52 is essential for CMA-induced PCa cell proliferation and stress resistance in vitro and in vivo . Furthermore, TPD52 is acetylated by KAT2B at K163, which is a process that can be antagonized by HDAC2. Inactivation of HDAC2 results in elevated TPD52 acetylation, which compromises the interaction between TPD52 and HSPA8, leading to impaired CMA function and tumor growth in vivo . Taken together, our findings reveal that acetylation-dependent regulation of TPD52 modulates CMA oncogenic function in PCa, thereby suggesting the possibility of targeting the TPD52-mediated CMA pathway to control the progression of PCa. Abbreviations : CMA: chaperone-mediated autophagy; HDAC2: histone deacetylase 2; HSPA8/HSC70: heat shock protein family A (Hsp70) member 8; KAT2B: lysine acetyltransferase 2B; LAMP2A: lysosomal associated membrane protein 2A; PCa: prostate cancer; TPD52: tumor protein D52